bauHof NGS – Poetics of circular construction (EAAE Annual Conference Proceedings, 2024)
The project “bauHof NGS” challenges conventional architectural approaches by adopting the concept of “form follows availability” and circular design methodologies. These methodologies allow students to move beyond the traditional linear process of design and construction, where design typically precedes materials selection. Instead, they engaged in a reciprocal relationship where the materials themselves influence and shape the design.Through this interaction between body and materials, questions relevant to the design are negotiated and decisions are made that are represented in drawings or models, and vis-à-vis. This hands-on approach broadens students’ understanding of circularity across dimensions of materials, construction and society based on real-world experiences. The necessity of rethinking the conventional linear model of production, use and disposal was a key focus throughout the semester.These learning experiences challenge the traditional hierarchical relationship between design and construction, theory and practice, planning and execution. They go beyond conventional classroom teaching to prepare students to make a meaningful contribution to creating a more resilient built environment.